2015
DOI: 10.1128/jvi.03069-14
|View full text |Cite
|
Sign up to set email alerts
|

Heterosubtypic Antibodies to Influenza A Virus Have Limited Activity against Cell-Bound Virus but Are Not Impaired by Strain-Specific Serum Antibodies

Abstract: The majority of influenza virus-specific antibodies elicited by vaccination or natural infection are effective only against the eliciting or closely related viruses. Rare stem-specific heterosubtypic monoclonal antibodies (hMAbs) can neutralize multiple strains and subtypes by preventing hemagglutinin (HA)-mediated fusion of the viral membrane with the endosomal membrane. The epitopes recognized by these hMAbs are therefore considered promising targets for the development of pan-influenza virus vaccines. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…Previous work has indicated that HA stalk-binding antibodies appear to be capable of accessing their epitope on virions (43), and thus their inferior potency is likely due to their inability to inhibit HA bind- ing to cell surface receptors: the robust means of neutralization achieved by HA head-binding antibodies (37). A recent study has also suggested that stalk-binding monoclonal antibodies have limited activity against cell-bound viruses, which would further limit their neutralization potency (44). Despite this inferior capacity to neutralize virus, passive transfer experiments in mice have demonstrated a strong propensity for these antibodies to activate antibody-dependent cellular cytotoxicity (ADCC), which correlates with enhanced protection in vivo (13).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has indicated that HA stalk-binding antibodies appear to be capable of accessing their epitope on virions (43), and thus their inferior potency is likely due to their inability to inhibit HA bind- ing to cell surface receptors: the robust means of neutralization achieved by HA head-binding antibodies (37). A recent study has also suggested that stalk-binding monoclonal antibodies have limited activity against cell-bound viruses, which would further limit their neutralization potency (44). Despite this inferior capacity to neutralize virus, passive transfer experiments in mice have demonstrated a strong propensity for these antibodies to activate antibody-dependent cellular cytotoxicity (ADCC), which correlates with enhanced protection in vivo (13).…”
Section: Discussionmentioning
confidence: 99%
“…HA stem antibodies protect by (i) preventing viral entry by blocking the fusion of host cell membrane and viral membrane (29), (ii) reducing viral egress by blocking neuraminidase activity through steric hindrance (30)(31)(32), and (iii) FcR-mediated induction of antibody-dependent cellular cytotoxicity (ADCC), antibody-dependent cellular phagocytosis and reactive oxygen species production (33)(34)(35). Several human-derived broadly neutralizing anti-stem antibodies have been identified against either influenza group 1 (36)(37)(38)(39) or group 2 (38,(40)(41)(42) or both groups (40,(43)(44)(45)(46)(47)(48)(49)(50) or even against both influenza A and B subtypes (51). The identification of these antibodies was an incentive to develop vaccines, which are discussed below.…”
Section: Hemagglutinin Stem-a Promising Universal Vaccine Targetmentioning
confidence: 99%
“…In fact, the stem region has become a main target for development of novel treatments using either antibody-based vaccine design or passive immunotherapy. So far, several bnAbs capable of neutralizing multiple serotypes of influenza A virus within group 1 and/or group 2 have been isolated from immunized mice, phage libraries, memory B or plasma cells of immune donors 12 13 14 15 16 17 18 19 20 21 . Most bnAbs, such as F10 (ref.…”
mentioning
confidence: 99%